Secretory IgA and T Cells Targeting SARS-CoV-2 Spike Protein Are Transferred to the Breastmilk Upon mRNA Vaccination - Gonçalves, J (2022)
In view of the scarcity of data to guide decision making, we evaluated how BNT162b2 and mRNA-1273 vaccines affect the immune response in lactating women and the protective profile of breastmilk. Compared with controls, lactating women had a higher frequency of circulating RBD memory B cells and higher anti-RBD antibody titers but similar neutralizing capacity. We show that upon vaccination, immune transfer to breastmilk occurs through a combination of anti-spike secretory IgA (SIgA) antibodies and spike-reactive T cells. Although we found that the concentration of anti-spike IgA in breastmilk might not be sufficient to directly neutralize SARS-CoV-2, our data suggest that cumulative transfer of IgA might provide the infant with effective neutralization capacity. Our findings put forward the possibility that breastmilk might convey both immediate (through anti-spike SIgA) and long-lived (via spike-reactive T cells) immune protection to the infant. Further studies are needed to address this possibility and to determine the functional profile of spike T cells.